ADF Winter School-An exciting concept of the Arbeitsgemeinschaft Dermatologische Forschung to connect young scientists and clinician scientists in Dermatology at the top of Germany - Yazdi, Amir S.; Barlin, Meltem; Boehm, Katharina; Gendrisch, Fabian; Ghorbanalipoor, Saeedeh; Haeberle, Stefanie; Hamel, Annamarie; Huening, Svea; Huettner, Clemens; Iwanova, Irina; Kanaki, Theodora; Kimeswenger, Susanne; et al. (Experimental Dermatology, 2017)
EVALuna2:35411

Arming T cells with a gp100-specific TCR and a CSPG4-specific CAR using combined DNA-and RNA-based receptor transfer - Simon, Bianca; Harrer, Dennis C.; Schuler-Thurner, Beatrice; Schuler, Gerold; Uslu, Ugur (Cancers, 2019)
Tumor cells can develop immune escape mechanisms to bypass T cell recognition, e.g., antigen loss or downregulation of the antigen presenting machinery, which represents a major challenge in adoptive T cell therapy. To counteract these mechanisms, we transferred not only one, but two receptors into the same T cell to generate T cells expressing two additional receptors (TETARs). We generated these TETARs by lentiviral transduction of a gp100-specific T cell receptor (TCR) and subsequent electroporation of mRNA encoding a second-generation CSPG4-specific chimeric antigen receptor (CAR). Following pilot experiments to optimize the combined DNA-and RNA-based receptor transfer, the functionality of TETARs was compared to T cells either transfected with the TCR only or the CAR only. After transfection, TETARs clearly expressed both introduced receptors on their cell surface. When stimulated with tumor cells expressing either one of the antigens or both, TETARs were able to secrete cytokines and showed cytotoxicity. The confirmation that two antigen-specific receptors can be functionally combined using two different methods to introduce each receptor into the same T cell opens new possibilities and opportunities in cancer immunotherapy. For further evaluation, the use of these TETARs in appropriate animal models will be the next step towards a potential clinical use in cancer patients.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Antigen loss; Cancer; Chimeric antigen receptor; Electroporation; Immune escape; Immunotherapy; Lentiviral transduction; Lentivirus; Melanoma

Autoimmune Colitis and Subsequent CMV-induced Hepatitis After Treatment With Ipilimumab - Uslu, Ugur; Agaimy, Abbas; Hundorfean, Gheorghe; Harrer, Thomas; Schuler, Gerold; Heinzerling, Lucie (Journal of Immunotherapy, 2015)
Ipilimumab, a humanized CTLA-4 antibody, improves overall survival in patients with metastatic melanoma. However, immune-related adverse effects occur in about 65% of ipilimumab-treated patients and have to be adequately managed. A 55-year-old patient developed grade 3 autoimmune colitis 7 weeks after initiation of ipilimumab treatment and subsequently hepatitis with grade 3 elevation of transaminases and ?-glutamyl transferase. Colitis manifested with up to 18 watery and bloody stools per day and severe attacks of abdominal pain. After exclusion of infectious causes, immunosuppression with corticosteroids was initiated. Because of recurrent abdominal pain, spontaneous perforation of the colon had to be excluded. Elevated liver function tests (grade 3 CTCAE) occurred and differential diagnosis included immune-mediated, toxic, and viral hepatitis. It is interesting to note that, not an immune-mediated but a cytomegalovirus-induced hepatitis was diagnosed by serum blood tests and liver biopsy and was subsequently successfully treated. Careful elaboration of the patient under immunotherapy was essential as further immunosuppression mandatory for autoimmune hepatitis would have worsened the viral hepatitis. In conclusion, cytomegalovirus reactivation should be included in the differential in patients under immunotherapy with checkpoint inhibitors and has to be considered as a cause for morbidity.
EVALuna2:1966

Automated closed-system manufacturing of human monocyte-derived dendritic cells for cancer immunotherapy - Erdmann, Michael; Uslu, Ugur; Wiesinger, Manuel; Bruening, Mareke; Altmann, Tobias; Strasser, Erwin; Schuler, Gerold; Schuler-Thurner, Beatrice (Journal of Immunological Methods, 2018)
Dendritic cell (DC)-based vaccines have been successfully used for immunotherapy of cancer and infections. A major obstacle is the need for high-level class A cleanroom cGMP facilities for DC generation. The CliniMACS Prodigy® (Prodigy) represents a new platform integrating all GMP-compliant manufacturing steps in a closed system for automated production of various cellular products, notably T cells, NK cells and CD34+ cells. We now systematically tested its suitability for producing human mature monocyte-derived DCs (Mo-DCs), and optimized it by directly comparing the Prodigy approach to our established standard production of Mo-DCs from elutriated monocytes in dishes or bags. Upon step-by-step identification of an optimal cell concentration for the Prodigy's CentriCult culture chamber, the total yield (% of input CD14+ monocytes), phenotype, and functionality of mature Mo-DCs were equivalent to those generated by the standard protocol. Technician's labor time was comparable for both methods, but the Prodigy approach significantly reduced hands-on time and high-level clean room resources. In summary, using our optimized conditions for the CliniMACS Prodigy, human Mo-DCs for clinical application can be generated almost automatically in a fully closed system. A significant drawback of the Prodigy approach was, however, that due to the limited size of the CentriCult culture chamber, in contrast to our standard semi-closed elutriation approach, only one fourth of an apheresis could be processed at once.
EVALuna2:203616

Automated Good Manufacturing Practice–compliant generation of human monocyte-derived dendritic cells from a complete apheresis product using a hollow-fiber bioreactor system overcomes a major hurdle in the manufacture of dendritic cells for cancer vaccines - Uslu, Ugur; Erdmann, Michael; Wiesinger, Manuel; Schuler, Gerold; Schuler-Thurner, Beatrice (Cytotherapy, 2019)
Background: Although dendritic cell (DC)–based cancer vaccines represent a promising treatment strategy, its exploration in the clinic is hampered due to the need for Good Manufacturing Practice (GMP) facilities and associated trained staff for the generation of large numbers of DCs. The Quantum bioreactor system offered by Terumo BCT represents a hollow-fiber platform integrating GMP-compliant manufacturing steps in a closed system for automated cultivation of cellular products. In the respective established protocols, the hollow fibers are coated with fibronectin and trypsin is used to harvest the final cell product, which in the case of DCs allows processing of only one tenth of an apheresis product. Materials and Results: We successfully developed a new protocol that circumvents the need for fibronectin coating and trypsin digestion, and makes the Quantum bioreactor system now suitable for generating large numbers of mature human monocyte-derived DCs (Mo-DCs) by processing a complete apheresis product at once. To achieve that, it needed a step-by-step optimization of DC-differentiation, e.g., the varying of media exchange rates and cytokine concentration until the total yield (% of input CD14+ monocytes), as well as the phenotype and functionality of mature Mo-DCs, became equivalent to those generated by our established standard production of Mo-DCs in cell culture bags. Conclusions: By using this new protocol for the Food and Drug Administration–approved Quantum system, it is now possible for the first time to process one complete apheresis to automatically generate large numbers of human Mo-DCs, making it much more feasible to exploit the potential of individualized DC-based immunotherapy.
CRIS-Team Scopus Importer:2019-11-12
Keywords: adoptive cell transfer; cell therapy; cellular therapy; dendritic cell vaccine; dendritic cells; immunotherapy; monocyte-derived dendritic cells; vaccines

Blood eosinophilia is an on-treatment biomarker in patients with solid tumors undergoing dendritic cell vaccination with autologous tumor-RNA - Moreira, Alvaro; Erdmann, Michael; Uslu, Ugur; Vass, Verona; Schuler, Gerold; Schuler-Thurner, Beatrice (Pharmaceutics, 2020)
Background: The approvals of immune checkpoint inhibitors for several cancer types and the rapidly growing recognition that T cell-based immunotherapy significantly improves outcomes for cancer patients led to a re-emergence of cancer vaccines, including dendritic cell (DC)-based immunotherapy. Blood and tissue biomarkers to identify responders and long-term survivors and to optimize cost and cost-effectiveness of treatment are greatly needed. We wanted to investigate whether blood eosinophilia is a predictive biomarker for patients with solid tumors receiving vaccinations with DCs loaded with autologous tumor-RNA. Methods: In total, 67 patients with metastatic solid tumors, who we treated with autologous monocyte-derived DCs transfected with total tumor mRNA, were serially analyzed for eosinophil counts and survival over the course of up to 14 years. Eosinophilic counts were performed on peripheral blood smears. Results: Up to 87% of the patients treated with DC-based immunotherapy experienced at least once an eosinophilia of ≥ 5% after initiation of therapy; 61 % reached levels of ≥ 10% eosinophils, and 13% of patients showed eosinophil counts of 20% or above. While prevaccination eosinophil levels were not associated with survival, patients with blood eosinophilia at any point after initiation of DC-based immunotherapy showed a trend towards longer survival. There was a statistically significant difference for the patients with eosinophil counts of 20% or more (p = 0.03). In those patients, survival was prolonged to a median of 58 months (range 2-111 months), compared to a median of 20 months (range 0-119 months) in patients with lower eosinophil counts. In 12% of the patients, an immediate increase in eosinophil count of at least 10 percentage points could be detected after the first vaccine, which also appeared to correlate with survival (65 vs. 24 months; p = 0.06). Conclusion: Blood eosinophilia appears to be an early, on-therapy biomarker in patients with solid tumors undergoing vaccination with RNA-transfected DC, specifically autologous tumor mRNA-transfected DC vaccines, and it correlates with long-term patient outcome. Eosinophilia should be systematically investigated in future trials.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Biomarkers; Dendritic cell vaccines; Eosinophils

CAR-T cell therapy in melanoma: A future success story? - Simon, Bianca; Uslu, Ugur (Experimental Dermatology, 2018)
Chimeric antigen receptor (CAR)-T cells are one of the impressive recent success stories of anti-cancer immunotherapy. Especially in haematological malignancies, this treatment strategy has shown promising results leading to the recent approval of two CAR-T cell constructs targeting CD19 in the United States and the European Union. After the huge success in haematological cancers, the next step will be the evaluation of its efficacy in different solid tumors, which is currently investigated in preclinical as well as clinical settings. A commonly examined tumor model in the context of immunotherapy is melanoma, since it is known for its immunogenic features. However, the first results of CAR-T cell therapy in solid tumors did not reveal the same impressive outcomes that were observed in haematological malignancies, as engineered cells need to cope with several challenges. Obstacles include the lack of migration of CAR-T cells from blood vessels to the tumor site as well as the immunosuppressive tumor microenvironment within solid tumors. Another hurdle is posed by the identification of an ideal target antigen to avoid on-target/off-tumor toxicities. Regarding immune escape mechanisms, which can be developed by tumor cells to bypass immune recognition, the observation of antigen loss should also be considered. This article gives an overview of the challenges displayed in CAR-T cell therapy for the use in solid tumors and discusses different new strategies and approaches that deal with these problems in order to improve CAR-T cell therapy, particularly for its use in melanoma.
EVALuna2:203618

CAR-T-Zellen auf dem Weg zur praktischen Anwendung in der dermatologischen Onkologie - Uslu, Ugur (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-03-19

Combining a CAR and a TCR to generate T cells expressing two additional receptors (TETARs) for melanoma immunotherapy - Uslu, Ugur; Gerer, K.; Hoyer, S.; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (2016)
EVALuna2:19613

Combining a chimeric antigen receptor and a conventional T-cell receptor to generate T cells expressing two additional receptors (TETARs) for a multi-hit immunotherapy of melanoma. - Uslu, Ugur; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (Experimental Dermatology, 2016)
The adoptive transfer of engineered T cells represents an important approach in immunotherapy of melanoma. However, relapse of the tumor can occur due to immune-escape mechanisms developed by the tumor cells, for example antigen loss, downregulation of the major histocompatibility complex presentation machinery and defects in antigen processing. To counteract these mechanisms, we combined a T-cell receptor and a chimeric antigen receptor, specific for different common melanoma antigens, gp100 (PMEL) and MCSP (HMW-MAA), to generate functional CD8(+) T cells expressing two additional receptors (TETARs) by electroporation of receptor-encoding mRNA. These TETARs produced cytokines and were lytic upon recognition of each of their cognate antigens, while no reciprocal inhibition of the receptors occurred. When stimulated with target cells, which express both antigens, an enhanced effect was suggested. The confirmation that chimeric antigen receptors and T-cell receptors can be functionally combined opens up new avenues in cancer immunotherapy, and the generation of TETARs helps by-passing major mechanisms by which tumor cells escape immune recognition.
EVALuna2:19624

Comparison of the Serum Tumor Markers S100 and Melanoma-inhibitory Activity (MIA) in the Monitoring of Patients with Metastatic Melanoma Receiving Vaccination Immunotherapy with Dendritic Cells - Uslu, Ugur; Schliep, Stefan; Schliep, Klaus; Erdmann, Michael; Koch, Hans-Uwe; Parsch, Hans; Rosenheinrich, Stina; Anzengruber, Doris; Boßerhoff, Anja Katrin; Schuler, Gerold; Schuler-Thurner, Beatrice (Anticancer Research, 2017)
In patients with melanoma, early dissemination via lymphatic and hematogenous routes is frequently seen. Thus, besides clinical follow-up examination and imaging, reliable melanoma-specific serological tumor markers are needed.We retrospectively compared two serum markers for melanoma, S100 and melanoma-inhibitory activity (MIA), for monitoring of patients with metastatic melanoma under either adjuvant or therapeutic vaccination immunotherapy with dendritic cells (DC). Serum was obtained from a total of 100 patients (28 patients in stage III and 72 patients in stage IV, according to the American Joint Committee on Cancer 2002) at regular intervals during therapy, accompanied by follow-up imaging.When relapse was detected, both markers often remained within normal range. In contrast, in patients with metastatic measurable disease receiving therapeutic and not adjuvant DC vaccination, an increase of both markers was a strong indicator for disease progression. When comparing both markers in the whole study population, MIA showed a superior sensitivity to detect disease progression.S100 and MIA are highly sensitive tumor markers for monitoring of patients with melanoma with current metastases, but less sensitive for monitoring of tumor-free patients. In the current study, MIA had a slightly superior sensitivity to detect progressive disease compared to S100 and seems to be more useful in monitoring of patients with metastatic melanoma receiving immunotherapy.
EVALuna2:4755

Crusted Nodules on the Lower Left Arm in a Traveller Returning from South America: A Quiz. Furuncular myiasis - Uslu, Ugur; Erdmann, Michael; Schliep, Stefan; Sticherling, Michael (Acta Dermato-Venereologica, 2018)
EVALuna2:34409

Driving CAR T cells towards dermatologic oncology - Uslu, Ugur (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Whereas approximately half of metastatic melanoma patients benefit from combined immune checkpoint inhibition targeting cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and Programmed cell death protein 1 (PD-1), for those who do not respond, further strategies and treatment options need to be developed. Thus, focus is turning to the use of chimeric antigen receptor (CAR) T cells, a novel therapy that has not yet achieved a major breakthrough in solid tumors despite the impressive response rates reported for their use in hematologic malignancies. In melanoma and other solid tumor entities, different problems still need to be addressed to improve this therapy, with mechanisms to counteract tumor escape being one of them. In this context, we could show the feasibility of combining two different transfection methods - lentiviral transduction and RNA-electroporation - for equipping the same T lymphocyte with two different tumor antigen-specific receptors. While further analysis is required to transfer this novel strategy from bench to bedside, appropriate target antigens that avoid on-target/off-tumor toxicities and additional optimization to increase CAR T cell power are also needed to maximize their potential use in dermatologic oncology.
CRIS-Team WoS Importer:2021-03-12

Effectiveness of an employee skin cancer screening program for secondary prevention - Uslu, Ugur; Hees, Felix; Winnik, Eva; Uter, Wolfgang; Sticherling, Michael (Cutis, 2016)
Incidences of UV-induced skin cancer are continuously increasing. For this reason, early diagnosis is becoming more important. In this study, 783 employees of a technical company participated in an employee skin cancer screening program, which consisted of a physical examination for benign and malignant skin lesions and premalignant conditions. To ensure the quality of the examinations, screening was only performed by 5 trained dermatologists. Participants also were asked to complete a standardized questionnaire prior to examination. A total of 661 skin lesions were diagnosed among 48% of participants; 12.8% of participants exhibited 50 or more melanocytic nevi and the risk for developing skin cancer was categorized as at least moderate for 64.9%. Additionally, 84.4% of participants with at least 1 skin lesion were advised to have a checkup within 1 year. The high rate of suspicious nevi detected in this study suggested that employee skin cancer screening programs are effective and also should be recommended at companies where employees are not at increased risk for developing skin cancer due to the nature of their work (eg, those who work outdoors). Despite the comparatively selective and young study population, these examinations provide evidence of the importance of skin cancer screening for the wider population.
EVALuna2:5563

Enhancing lentiviral transduction to generate melanoma-specific human T cells for cancer immunotherapy - Simon, Bianca; Harrer, Dennis C.; Thirion, Christian; Schuler-Thurner, Beatrice; Schuler, Gerold; Uslu, Ugur (Journal of Immunological Methods, 2019)
Introduction of a tumor antigen-specific T cell receptor (TCR) into patient-derived lymphocytes has already exhibited promising results for the treatment of melanoma and other malignancies in clinical trials. However, insufficient or unsuccessful ex vivo manufacturing of engineered T cells due to low expansion and/or transduction rate can still be observed in some patients. Thus, we isolated human CD8+ T cells from healthy donors and equipped them with a gp100-specific TCR using a lentiviral construct in combination with a novel chemical lentiviral transduction enhancer (Lentiboost) to increase the rate of transduced cells. Following experiments to determine the ideal multiplicity of infection (MOI) and to analyze the efficacy of the transduction enhancer using a GFP-encoding lentivirus, we analyzed in the next step the transduction rate, cell count, and functionality of gp100 TCR-transduced T cells, i.e. antigen-specific cytokine secretion and lytic capacity. In order to increase the number of transduced cells, antigen-specific stimulation was performed, either once for 1 week (1st activation) or twice for another week (2nd activation). In general, each cycle of antigen-specific stimulation resulted in expansion of TCR-positive cells, while no further significant increase of transduced cells was observed after 2nd activation. Cytokine production pattern of transduced cells after antigen encounter, however, revealed significant antigen-specific secretion of TNF and IFNγ after the 1st as well as the 2nd activation. Furthermore, TCR T cells, either activated once or twice, showed significant cytotoxicity towards antigen-positive tumor cells. Taken together, these results show that it is feasible to transduce human T cells using a lentiviral construct in combination with this novel lentiviral transduction enhancer, which shows potential in the growing field of cancer immunotherapy.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Adoptive T cell therapy; gp100; Lentiboost; Lentivirus; T cell receptor; Tumor antigen

Eosinophilic polymorphic and pruritic eruption associated with radiotherapy: case report and overview of disease characteristics - Löbelenz, L.; Schliep, S.; Wörl, Petra; Uslu, Ugur (Clinical and Experimental Dermatology, 2019)
CRIS-Team Scopus Importer:2019-06-25

Factors Influencing Disease Progression in Patients with Head and Neck Melanoma - Uslu, Ugur; Schuler, Gerold; Breuninger, Helmut (Anticancer Research, 2017)
BACKGROUND: Histological parameters as well as the status of sentinel lymph node are known to be strong prognostic factors in patients with melanoma. PATIENTS AND METHODS: In this study, we retrospectively analyzed 1,384 patients who were diagnosed with head and neck melanoma between 1976 and 2010 regarding prognostic factors [tumor thickness, level of invasion, sentinel lymph node (SLN) status, ulceration, histological subtype, localization, and gender], overall survival, and disease-free survival. RESULTS: Patients who developed metastases had a significantly thicker tumor than patients without metastases. Additionally, a thicker tumor was often associated with a higher level of invasion (Clark level). There was no overall survival benefit in patients who underwent SLN dissection when compared to patients who did not (p=0.07). Compared to SLN-negative patients, patients with SLN involvement had a significantly shorter disease-free period (p<0.001) and shorter overall survival time (p<0.001). CONCLUSION: In summary, tumor thickness is the most important prognostic factor. SLN dissection does not affect the overall survival of patients with melanoma. However, a positive SLN is a marker for a worse outcome in these patients.
EVALuna2:34319

Fasten the seat belt: Increasing safety of CAR T-cell therapy - Simon, Bianca; Uslu, Ugur (Experimental Dermatology, 2020)
After the recent success and approvals of chimeric antigen receptor (CAR) T cells in haematological malignancies, its efficacy is currently evaluated in a broad spectrum of tumor entities including melanoma. However, severe and potentially life-threatening side effects like cytokine release syndrome, neurologic toxicities, and the competing risk of morbidity and mortality from the treatment itself are still a major limiting factor in the current CAR T-cell landscape. In addition, especially in solid tumors, the lack of ideal target antigens to avoid on-target/off-tumor toxicities also restricts its use. While various groups are working on strategies to boost CAR T-cell efficacy, mechanisms to increase engineered T-cell safety should not move out of focus. Thus, the aim of this article is to summarize and to discuss current and potential future strategies and mechanisms to increase CAR T-cell safety in order to enable the wide use of this promising approach in melanoma and other tumor entities.
CRIS-Team Scopus Importer:2020-07-17
Keywords: adoptive T-cell therapy; cancer; chimeric antigen receptor; cytokine release syndrome; neurotoxicity

Fumaric Acid Esters and TNF alpha Inhibitors - Do they affect the Fertility of male Patients with Psoriasis? - Heppt, Franz; Colsmann, A.; Maronna, A.; Uslu, Ugur; Heppt, M.; Kiesewetter, Franklin; Sticherling, Michael (2017)
EVALuna2:34352

gamma/delta T cells RNA-transfected with a T-cell receptor and a chimeric antigen receptor specific for melanoma - Harrer, D.; Simon, B.; Schuler, Gerold; Uslu, Ugur; Hoyer, S.; Dörrie, Jan; Schaft, Niels (2016)
EVALuna2:19612

Generation of CD8(+) T cells expressing two additional T-cell receptors (TETARs) for personalised melanoma therapy. - Hoefflin, Sandra; Prommersberger, Sabrina; Uslu, Ugur; Schuler, Gerold; Schmidt, Christopher W.; Lennerz, Volker; Dörrie, Jan; Schaft, Niels (Cancer Biology & Therapy, 2015)
Adoptive T-cell therapy of cancer often fails due to the tumor cells' immune escape mechanisms, like antigen loss or down-regulation. To anticipate immune escape by loss of a single antigen, it would be advantageous to equip T cells with multiple specificities. To study the possible interference of 2 T-cell receptors (TCRs) in one cell, and to examine how to counteract competing effects, we generated TETARs, CD8(+) T cells expressing two additional T-cell receptors by simultaneous transient transfection with 2 TCRs using RNA electroporation. The TETARs were equipped with one TCR specific for the common melanoma antigen gp100 and one TCR recognizing a patient-specific, individual mutation of CCT6A (chaperonin containing TCP1, subunit 6A) termed "CCT6A(m) TCR." These CD8(+) T cells proved functional in cytokine secretion and lytic activity upon stimulation with each of their cognate antigens, although some reciprocal inhibition was observed. Murinisation of the CCT6A(m) TCR increased and prolonged its expression and increased the lytic capacity of the dual-specific T cells. Taken together, we generated functional, dual-specific CD8(+) T cells directed against a common melanoma-antigen and an individually mutated antigen for the use in personalised adoptive T-cell therapy of melanoma. The intended therapy would involve repetitive injections of the RNA-transfected cells to overcome the transiency of TCR expression. In case of autoimmunity-related side effects, a cessation of treatment would result in a disappearance of the introduced receptors, which increases the safety of this approach.
EVALuna2:19563

GMP-compliant human monocyte-derived dendritic cells for cancer vaccination generated by using the Quantum (R) hollow fiber bioreactor system - Uslu, Ugur; Uslu, U.; Erdmann, M.; Wiesinger, M.; Schuler, Gerold; Schuler-Thurner, Beatrice (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2020-01-28

Influence of TNF-alpha inhibitors and fumaric acid esters on male fertility in psoriasis patients - Heppt, Franz; Colsman, A.; Maronna, A.; Uslu, Ugur; Heppt, M. V.; Kiesewetter, Franklin; Sticherling, Michael (Journal of the European Academy of Dermatology and Venereology, 2017)
OBJECTIVE: Is there any influence of a therapy with TNF-alpha inhibitors or fumaric acid esters and of disease activity status on male fertility and sperm quality in patients with psoriasis? METHODS: In this monocentric, open-label, prospective study, semen samples were collected from patients receiving either TNF-alpha inhibitors or fumaric acid esters for moderate-to-severe plaque psoriasis. Semen was analysed at baseline before onset of the systemic therapy and monitored every 3 months under therapy. Sperm parameters were assessed according to the current WHO definitions. RESULTS: In total, 101 semen specimens from 27 patients were obtained. Mean Psoriasis Area and Severity Index (PASI) score at baseline was 11.05. Only 14.8% of patients showed a normozoospermia without any other abnormal seminal values. 85.2% of patients had at least one sperm/seminal abnormality, including two patients showing an azoospermia. Interestingly, 48.1% showed sperm parameters indicative of genital tract inflammation. Therapy with TNF-alpha inhibitors or fumaric acid esters did not have any negative effects on relevant sperm parameters such as mean total sperm number, sperm concentration, total and progressive motility. No major gonadal dysfunction was observed in any patient. CONCLUSION: At baseline, many patients with psoriasis showed abnormal semen/sperm parameters and remarkably elevated leukocytes and values of seminal polymorphonuclear elastase, indicating a genital tract inflammation. Thus, genital tract inflammation may represent an important comorbidity of psoriasis, little attention paid to so far. Regarding treatment with TNF-alpha inhibitors or fumaric acid esters, no major negative (side-) effects on sperm quality were observed.
EVALuna2:34337

Nachwuchs für die Dermatologie begeistern: Die DDG auf dem Bundeskongress der Bundesvertretung der Medizinstudierenden in Deutschland e. V - Huening, Svea; Rode, Susen; Nashan, Dorothee; Emmert, Steffen; Uslu, Ugur (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
EVALuna2:212829

Panniculitis under successful targeted inhibition of the MAPK/ERK signaling pathway in a patient with BRAF V600E-mutated spindle cell oncocytoma of the pituitary gland - Sollfrank, Lukas; Lettmaier, Sebastian; Erdmann, Michael; Uslu, Ugur (Anticancer Research, 2019)
Background: Spindle cell oncocytoma (SCO) is a rare non-neuroendocrine neoplasm of the pituitary gland. In general, surgical excision and radiation therapy is performed. However, local recurrences are frequently seen, requiring repeated surgical and radio-oncological interventions. Thus, mutational analysis of the tumor and targeted therapy may represent a valuable therapy option in these patients. Case Report: A 38-year-old female patient with past medical history of 6 surgeries (two transsphenoidal and four transcranial), radiation therapy, and chemoradiation therapy due to several recurrences of a SCO, presented for follow-up imaging. MRI of the brain showed growth of a tumor in the right parasellar region consistent with a new local recurrence, which due to its size and location was considered to be not resectable. Molecular analysis of a previously surgically removed tumor showed a BRAF V600E mutation and thus, combined targeted inhibition of the MAPK/ERK signaling pathway using a BRAF inhibitor and a MEK inhibitor was started. Due to drug-induced panniculitis, MEK inhibitor had to be stopped and BRAF inhibitor only was continued, which was well tolerated by the patient. Subsequent imaging revealed tumor regression already four weeks after therapy initiation and no disease progression has been observed to date. Conclusion: A SCO patient with BRAF V600E mutation was successfully treated using targeted inhibition of the MAPK/ERK signaling pathway. Under therapy, tumor regression was observed and the patient has been free of progressive disease for more than two years now. Thus, mutational analysis and targeted inhibition may offer an effective treatment option for SCO patients, while potential side-effects to this therapy, like observed in our case, can occur and needs to be adequately treated.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Adenoma; BRAF; Cobimetinib; Dabrafenib; MEK; Panniculitis; Pituicytoma; Targeted therapy; Trametinib; Vemurafenib

Peripheral PD-1+CD56+ T-cell frequencies correlate with outcome in stage IV melanoma under PD-1 blockade - Bochem, Jonas; Zelba, Henning; Amaral, Teresa; Spreuer, Janine; Soffel, Daniel; Eigentler, Thomas; Wagner, Nikolaus Benjamin; Uslu, Ugur; Terheyden, Patrick; Meier, Friedegund; Garbe, Claus; Pawelec, Graham; et al. (PLoS ONE, 2019)
Immune checkpoint blockade with anti-PD-1 antibodies is showing great promise for patients with metastatic melanoma and other malignancies, but despite good responses by some patients who achieve partial or complete regression, many others still do not respond. Here, we sought peripheral blood T-cell biomarker candidates predicting treatment outcome in 75 stage IV melanoma patients treated with anti-PD-1 antibodies. We investigated associations with clinical response, progression-free survival (PFS) and overall survival (OS). Univariate analysis of potential biological confounders and known biomarkers, and a multivariate model, was used to determine statistical independence of associations between candidate biomarkers and clinical outcomes. We found that a lower than median frequency of peripheral PD-1+CD56+ T-cells was associated with longer OS (p = 0.004), PFS (p = 0.041) and superior clinical benefit (p = 0.009). However, neither frequencies of CD56-CD4+ nor CD56-CD8+ T-cells, nor of the PD-1+ fraction within the CD4 or CD8 subsets was associated with clinical outcome. In a multivariate model with known confounders and biomarkers only the M-category (HR, 3.11; p = 0.007) and the frequency of PD-1+CD56+ T-cells (HR, 2.39; p = 0.028) were identified as independent predictive factors for clinical outcome under PD-1 blockade. Thus, a lower than median frequency of peripheral blood PD-1+CD56+ T-cells prior to starting anti-PD-1 checkpoint blockade is associated with superior clinical response, longer PFS and OS of stage IV melanoma patients.
CRIS-Team Scopus Importer:2019-08-27

Rapid development of cutaneous melanoma metastases after herpes zoster infection in a radiotherapy field - Uslu, Ugur; Schliep, S.; Erdmann, M. (Clinical and Experimental Dermatology, 2018)
Click for the corresponding questions to this CME article.
EVALuna2:34807

Risk Factors for Regional and Systemic Metastases in Patients with Sentinel Lymph Node-negative Melanoma - Erdmann, Michael; Sigler, Dominic; Uslu, Ugur; Göhl, Jonas; Grützmann, Robert; Schuler, Gerold; Schellerer, Vera (Anticancer Research, 2018)
BACKGROUND: Sentinel lymph node status is a strong prognostic factor in melanoma. However, up to 21% of sentinel lymph node-negative patients develop locoregional and distant metastases during follow-up. AIM: To analyze risk factors for locoregional and distant metastasis in patients with sentinel lymph node-negative melanoma. PATIENTS AND METHODS: A total of 545 patients underwent sentinel lymph node biopsy (SNB) between 2005 and 2013 at our hospital. Data for 449 patients with a negative SNB were analyzed regarding risk factors and development of metastases. Follow-up was performed until 2016. RESULTS: A total of 72 SNB-negative patients developed metastases, including 25 (34.7%) distant and 47 (63.3%) locoregional metastases. Locoregional metastases occurred earlier compared to distant metastases (with a mean of 24.2 and 23.5 months for regional lymph node and cutaneous metastases, respectively, vs. 31.4 months for distant metastases). Patients with metastases despite negative SNB had a greater tumor thickness (p=0.001), a higher rate of nodular melanoma (p=0.001), ulceration (p<0.001), and were older (p=0.05) compared to SNB-negative patients without subsequent metastases. Out of SNB-negative patients, 16% developed metastases. CONCLUSION: Close clinical follow-up including sonography of the draining lymph node region is mandatory for melanoma patients regardless of SNB status.
EVALuna2:203619

RNA-transfection of gamma/delta T cells with a chimeric antigen receptor or an alpha/ss T-cell receptor: a safer alternative to genetically engineered alpha/ss T cells for the immunotherapy of melanoma - Harrer, D.; Simon, B.; Fujii, S. I.; Kanako, S.; Uslu, Ugur; Schuler, Gerold; Gerer, K. F.; Hoyer, S.; Dörrie, Jan; Schaft, Niels (2017)
EVALuna2:34308

RNA-transfection of γ/δ T cells with a chimeric antigen receptor or an α/β T-cell receptor: a safer alternative to genetically engineered α/β T cells for the immunotherapy of melanoma - Harrer, Dennis C.; Simon, Bianca; Fujii, Shin-Ichiro; Shimizu, Kanako; Uslu, Ugur; Schuler, Gerold; Gerer, Kerstin F.; Hoyer, Stefanie; Dörrie, Jan; Schaft, Niels (BMC Cancer, 2017)
BACKGROUND: Adoptive T-cell therapy relying on conventional T cells transduced with T-cell receptors (TCRs) or chimeric antigen receptors (CARs) has caused substantial tumor regression in several clinical trials. However, genetically engineered T cells have been associated with serious side-effects due to off-target toxicities and massive cytokine release. To obviate these concerns, we established a protocol adaptable to GMP to expand and transiently transfect γ/δ T cells with mRNA. METHODS: PBMC from healthy donors were stimulated using zoledronic-acid or OKT3 to expand γ/δ T cells and bulk T cells, respectively. Additionally, CD8+ T cells and γ/δ T cells were MACS-isolated from PBMC and expanded with OKT3. Next, these four populations were electroporated with RNA encoding a gp100/HLA-A2-specific TCR or a CAR specific for MCSP. Thereafter, receptor expression, antigen-specific cytokine secretion, specific cytotoxicity, and killing of the endogenous γ/δ T cell-target Daudi were analyzed. RESULTS: Using zoledronic-acid in average 6 million of γ/δ T cells with a purity of 85% were generated from one million PBMC. MACS-isolation and OKT3-mediated expansion of γ/δ T cells yielded approximately ten times less cells. OKT3-expanded and CD8+ MACS-isolated conventional T cells behaved correspondingly similar. All employed T cells were efficiently transfected with the TCR or the CAR. Upon respective stimulation, γ/δ T cells produced IFNγ and TNF, but little IL-2 and the zoledronic-acid expanded T cells exceeded MACS-γ/δ T cells in antigen-specific cytokine secretion. While the cytokine production of γ/δ T cells was in general lower than that of conventional T cells, specific cytotoxicity against melanoma cell lines was similar. In contrast to OKT3-expanded and MACS-CD8+ T cells, mock-electroporated γ/δ T cells also lysed tumor cells reflecting the γ/δ T cell-intrinsic anti-tumor activity. After transfection, γ/δ T cells were still able to kill MHC-deficient Daudi cells. CONCLUSION: We present a protocol adaptable to GMP for the expansion of γ/δ T cells and their subsequent RNA-transfection with tumor-specific TCRs or CARs. Given the transient receptor expression, the reduced cytokine release, and the equivalent cytotoxicity, these γ/δ T cells may represent a safer complementation to genetically engineered conventional T cells in the immunotherapy of melanoma (Exper Dermatol 26: 157, 2017, J Investig Dermatol 136: A173, 2016).
EVALuna2:34316

Sarcoidosis Under Dendritic Cell Vaccination Immunotherapy in Long-term Responding Patients with Metastatic Melanoma - Uslu, Ugur; Erdmann, Michael; Schliep, Stefan; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Schuler-Thurner, Beatrice (Anticancer Research, 2017)
Sarcoidosis, a chronic inflammatory disorder, results from increased immune responses. Its development can be triggered in patients under immunotherapy, as activation of the immune system in these patients is desired. Since 1997, 249 patients with metastasized cutaneous melanoma (stage III and IV, AJCC 2009) have been treated with dendritic cell (DC)-based vaccines at our hospital. Three out of these patients were diagnosed with sarcoidosis after or during long-term DC vaccination therapy (1.20%). Metastatic disease was initially suspected based on the radiographic manifestation of lung masses or bilateral hilar lymphadenopathy. Histological assessment, however, revealed the appropriate diagnosis. Interestingly, all three patients are long-term responders and have remained free of metastatic or progressive disease for over a period of at least 4 years. In summary, sarcoidosis can occur in patients with cancer who have benefited from DC-based therapeutic vaccination and thus, its development, even with substantial delay, may be associated with successful anticancer immunotherapy.
EVALuna2:34321

Secondary syphilis infection under treatment with ustekinumab - Uslu, Ugur; Heppt, Franz; Sticherling, Michael (Clinical and Experimental Dermatology, 2017)
EVALuna2:34342

Sentinel Lymph Node Dissection in Head and Neck Melanoma has Prognostic Impact on Disease-Free and Overall Survival - Leiter, Ulrike; Eigentler, Thomas K.; Haefner, Hans-Martin; Krimmel, Michael; Uslu, Ugur; Keim, Ulrike; Weide, Benjamin; Breuninger, Helmut; Martus, Peter; Garbe, Claus (Annals of Surgical Oncology, 2015)
Sentinel lymph node biopsy (SLNB) plays an important role in the prognostic classification of melanoma and is now a standard staging procedure. However, due to the complex drainage pattern and the risk of site associated morbidity, the potential survival benefit of SLNB is controversial in head and neck (H&N) melanoma.Patients with primary H&N melanoma with a tumor thickness >=1.00 mm diagnosed in the Department of Dermatology, University of Tuebingen, Germany between 1991 and 2010 were included in this study. Regarding patterns of metastases, disease-free, and overall-survival, 259 patients with SLNB were compared retrospectively to 218 patients without SLNB.The detection of micrometastasis in SLN proved to be a significant prognostic factor in H&N patients [hazard ratio (HR) 3.69, p < 0.0001]. A significant improvement of recurrence-free survival (RFS, p = 0.011), regional lymph node metastasis-free survival (LFS, p = 0.007), and distant metastasis-free survival (DMSF, p = 0.015) was observed for patients with SLNB versus non-SLNB. Furthermore, a trend towards better overall survival (OS) was found (p = 0.053) for the SLNB group.SLNB improved prognostic outcome in H&N melanoma in terms of disease-free and distant metastases survival, reduced subsequent regional lymph node metastases, and showed a trend towards a better OS.
EVALuna2:19555

Skin and Soft Tissue Infections Caused by Mycobacterium chelonae: More Common Than Expected? - Uslu, Ugur; Boehm, Olga; Heppt, Franz; Sticherling, Michael (Acta Dermato-Venereologica, 2019)
Mycobacterium chelonae is a rapidly growing non-tuberculous mycobacterium, which causes infections of the human skin and soft tissue. Despite an increasing incidence of such infections, patients are often misdiagnosed. We report here 5 patients with cutaneous and/or soft tissue infection due to M. chelonae who were diagnosed and treated at our centre. Two of the 5 patients were on immunosuppressive treatment. While clinical presentations differed in each patient, all had a long history of skin lesions. In addition to careful history-taking, tissue biopsies were obtained for mycobacterial culture and histopathological examination. Culture-directed antibiotic therapy was initiated, which resulted in a slow, but continuous, healing of the lesions. In summary, M. chelonae infections are still relatively rare, but should be considered in both immunocompromised and immunocompetent patients with prolonged skin lesions resistant to standard antibiotic treatment. For diagnosis, tissue analysis for mycobacterial culture and histopathological examination, and once diagnosed, adequate antibiotic treatment, is needed.
CRIS-Team WoS Importer:2019-09-10

Späte Diagnose einer subkutanen Dirofilariose nach einem Mückenstich in Deutschland - Uslu, Ugur; Jahn, Julia; Erdmann, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
EVALuna2:35408

Step-by-step Improvement of mRNA-electroporated dendritic Cells in a Phase I / II Clinical Study in cutaneous Melanoma Patients: better Survival correlates with a higher Immunoscore and increased Expression of PEBP1 in the Blood - Dörrie, Jan; Schaft, Niels; Gross, S.; Ostalecki, Christian; Eberhardt, Martin; Vera-Gonzales, J.; Uslu, Ugur; Moreira, Alvaro; Koch, Elias; Kummer, Mirko; Erdmann, M.; Schliep, S.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Systemic therapy with calcitonin has positive clinical effects on systemic sclerosis in patients with cutaneous manifestations - Uslu, Ugur; Streiff, Laura; Sticherling, Michael (European Journal of Dermatology, 2018)
BACKGROUND: Calcitonin gene-related peptide (CGRP) is a vasodilatory neuropeptide that plays an important role in the blood vessels of heart and peripheral circulation, a lack of which may cause vasculopathies. OBJECTIVE: In this study, the clinical course of disease, as well as the efficacy, side effects, and patient satisfaction of systemic calcitonin therapy in patients with systemic sclerosis (SSc), was evaluated. METHODS: Forty-nine patients received repetitive intravenous calcitonin infusions as first-line treatment. The average number of cycles was 12.2 ± 10.3 over a period of 30 months (each cycle: 100 U/day over 10 days). Clinical examinations, laboratory tests, and organ imaging were performed before the start of, and at regular intervals during therapy in order to evaluate organ manifestations and the clinical course of the disease. In addition, patients' own experiences of the therapy, side effects, and therapy success were evaluated with standardized questionnaires. RESULTS: Over the course of the treatment, seven patients experienced improvements in their condition with a considerable reduction in digital ulceration and improved movement (14.3%). Pulmonary function in seven patients improved during the therapy (14.3%). With regards to side effects, nausea (41.7%), headaches (33.3%), fluctuations in blood pressure (29.2%), and flushing (29.2%) were observed. Overall, 45.8% of patients evaluated the therapy as good and 58.3% would undergo further courses of therapy with calcitonin. CONCLUSIONS: Systemic calcitonin treatment seems to have positive clinical effects on SSc and contributes to relieving symptoms, especially in patients with cutaneous manifestations. No severe side effects were reported during this study.
EVALuna2:34793

The Generation of CAR-Transfected Natural Killer T Cells for the Immunotherapy of Melanoma - Simon, Bianca; Wiesinger, Manuel; Maerz, Johannes; Wistuba-Hamprecht, Kilian; Weide, Benjamin; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (International Journal of Molecular Sciences, 2018)
Natural killer T (NKT) cells represent a cell subpopulation that combines characteristics of natural killer (NK) cells and T cells. Through their endogenous T-cell receptors (TCRs), they reveal a pronounced intrinsic anti-tumor activity. Thus, a NKT cell transfected with a chimeric antigen receptor (CAR), which recognizes a tumor-specific surface antigen, could attack tumor cells antigen-specifically via the CAR and additionally through its endogenous TCR. NKT cells were isolated from peripheral blood mononuclear cells (PBMCs), expanded, and electroporated with mRNA encoding a chondroitin sulfate proteoglycan 4 (CSPG4)-specific CAR. The CAR expression on NKT cells and their in vitro functionality were analyzed. A transfection efficiency of more than 80% was achieved. Upon stimulation with melanoma cells, CAR-NKT cells produced cytokines antigen-specifically. Compared with conventional CAR-T cells, cytokine secretion of CAR-NKT cells was generally lower. Specific cytotoxicity, however, was similar with CAR-NKT cells showing a trend towards improved cytotoxicity. Additionally, CAR-NKT cells could kill target cells through their endogenous TCRs. In summary, it is feasible to generate CAR-NKT cells by using mRNA electroporation. Their CAR-mediated cytotoxicity is at least equal to that of conventional CAR-T cells, while their intrinsic cytotoxic activity is maintained. Thus, CAR-NKT cells may represent a valuable alternative to conventional CAR-T cells for cancer immunotherapy.
EVALuna2:34785

The Generation of CAR-transfected NKT Cells for the Immunotherapy of Melanoma - Simon, B.; Wiesinger, M.; Marz, J.; Wistuba-Hamprecht, K.; Weide, B.; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (2018)
EVALuna2:34767

The simultaneous siRNA-mediated downregulation of inhibitory receptors to improve CAR-T cell immunotherapy of melanoma - Simon, B.; Harrer, D.; Weide, B.; Schuler, Gerold; Schuler-Thurner, Beatrice; Dörrie, Jan; Schaft, Niels; Uslu, Ugur (2017)
EVALuna2:34317

The simultaneous siRNA-mediated downregulation of PD-1 and CTLA-4 to improve CAR-T cell immunotherapy of melanoma - Simon, B.; Harrer, D.; Schuler-Thurner, Beatrice; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Uslu, Ugur (2018)
EVALuna2:34395

The siRNA-mediated downregulation of PD-1 alone or simultaneously with CTLA-4 shows enhanced in vitro CAR-T-cell functionality for further clinical development towards the potential use in immunotherapy of melanoma - Simon, Bianca; Harrer, Dennis C.; Schuler-Thurner, Beatrice; Schaft, Niels; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (Experimental Dermatology, 2018)
Chimeric antigen receptor (CAR)-T cells have been used successfully for cancer immunotherapy. While substantial tumor regression was observed in leukaemia and lymphoma, CAR therapy of solid tumors needs further improvement. A major obstacle to the efficiency of engineered T cells is posed by triggering of inhibitory receptors, for example programmed cell death protein 1 (PD-1) and cytotoxic T lymphocyte-associated protein 4 (CTLA-4), leading to an impaired antitumor activity. To boost CAR-T-cell function, we co-electroporated T cells with both, mRNA encoding a CAR specific for chondroitin sulphate proteoglycan 4 (CSPG4) and small-interfering RNAs (siRNAs) to downregulate PD-1 (siPD-1) and CTLA-4 (siCTLA-4). Flow cytometry revealed that activation-induced upregulation of both PD-1 and CTLA-4 was suppressed when compared to CAR-T cells electroporated with negative control siRNA. The siRNA transfection showed no influence on CAR expression of engineered T cells. Functionality assays were performed using PD-L1- and CD80-transfected melanoma cells endogenously expressing CSPG4. CAR-T cells transfected with siPD-1 alone showed improvement in cytokine secretion. Additionally, CAR-T cells transfected with either siPD-1 alone or together with siCTLA-4 exhibited a significantly increased cytotoxicity. No or only little effects were observed when CAR-T cells were co-transfected with siCTLA-4 only. Taken together, it is feasible to optimize CAR-T cells by co-transfection of CAR-encoding mRNA and siRNAs to downregulate inhibitory receptors. Our in vitro data indicate an improvement of the functionality of these CAR-T cells, suggesting that this strategy could represent a novel method to enhance CAR-T-cell immunotherapy of cancer.
EVALuna2:34375

The transfection of natural killer T cells with a tumor-antigen specific chimeric antigen receptor (CAR) for melanoma immunotherapy - Simon, B.; Wiesinger, M.; Maerz, J.; Wistuba-Hamprecht, K.; Weide, B.; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (EXPERIMENTAL DERMATOLOGY, 2019)
CRIS-Team WoS Importer:2019-03-26

Vaccination with dendritic Cells for metastasized Uveal Melanoma: immunological and clinical Responses - Moreira, Alvaro; Gross, S.; Uslu, Ugur; Dörrie, Jan; Kummer, Mirko; Schliep, S.; Sponagl, F.; Lischer, Christopher; Erdmann, M.; Heinzerling, Lucie; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13